A Self-review or a Friendly Debate over One Article - Miller, Jaroslav (Dějiny – teorie – kritika, 2007)
The author subjects Josef Hrdlička’s thoughts on the book Uzavřená společnost a její nepřátelé: Město středovýchodní Evropy, 1500–1700 [The Closed Society and Its Enemies: The City in Central Europe, 1500–1700] to critical examination. He draws attention to two shortcomings in Hrdlička’s review which led to a partial misinterpretation of his study. Josef Hrdlička refrains from a deep analysis of the theoretical underpinnings of Miller’s book, which are based on the explanatory potential of Popper’s concepts of open and closed societies. Besides, the author tries to furnish proof that the reviewer did not wholly respect the genre demarcation of the study, for he finds fault with the book for a purported lack of research methods; the application of such methods, however, would be proper to a different type of scholarly text.